IMPLIKATUR TUTURAN PARA TOKOH DALAM NOVEL KAMI (BUKAN) SARJANA KERTAS KARYA J.S. KHAIREN - Istiana Istiana; Sisilya Saman Madeten; Sesilia Seli (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to determine the speech implicatures of the characters in the novel (Kami) Bukan Sarjana Kertas by J.S. Khairen and implementation design in school learning. The method used in this research is a descriptive method with a qualitative form. J.S. Khairen's data analysis in the novel (Kami) Bukan Sarjana Kertas is the form of the character’s speeches that indicate the implicature’s type, form, and function. The analysis results found (1) types of implicatures, namely conventional implicatures and non-conventional implicatures. There are three types of non-conventional implicatures, general conversational implicatures, scaled conversational implicatures, and special conversational implicatures. (2) The form of implicature consists of six types; the form of implicature prohibits, the form of implicature declines, the form of implicature commands, the form of implicature asks, the form of implicature asserts, and the form of implicature complains. (3) Conventional implicature functions and unconventional implicature functions. Conventional implicature functions, namely representative implicature functions and expressive implicature functions. Non-conventional implicature functions include representative implicature functions, directive implicature functions, expressive implicature functions, commissive implicature functions, and intrinsic implicature functions. (4) The results of research from the novel (Kami) Bukan Sarjana Kertas J.S. Khairen has the opportunity to be implemented in learning literature in Senior High Scholl class XI in the odd terms at KD 3.9 and 4.9.